Assessing impacts of water harvesting techniques on the water footprint of sorghum in Western Sudan. (September 2016) - Ali, Abubaker B.; Hong, Li; Elshaikh, Nazar A.; Haofang, Yan
Improving the water footprint (WFP) of crops through the implementation of water harvesting techniques (WHT) can help save water and enhance crop production. This study investigated the impact of different WHTs on the green, blue and total WFP components of sorghum production in Western Sudan. Water harvesting was used as a tool for reducing water consumption and minimizing the WFP in two consecutive rainy seasons in 2012 and 2013. The average WFP for sorghum was estimated to be 1100 m 3 ton −1, with the green component providing the highest contribution. According to WFP analysis there were significant differences between WHT treatments ( p ≤ 0.05) with tide ridging providing the greatest reduction (79%) compared to other treatments including ridging (71%) and basin (58%), respectively. A similar trend was found regarding soil moisture, fresh, dry matter and productivity (yield). The blue water component has an important impact on the total WFP for sorghum production.